Texas terror - Bradbury, Robert N. (Robert North); Wayne, John, 1907-1979; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1935)
Sheriff John Higgins quits and goes into prospecting after he thinks he has killed his best friend in shooting it out with robbers. He encounters his dead buddy's sister and helps her run her ranch. Then she finds out about his past. --
John Wayne, Lucille Brown, Leroy Mason, Fern Emmett, George Hayes, Bufflo Bill, Jr., John Ince, Henry Roguemore, Jack Duffy.
Cinematographer, William Hyer; editor, Carl Pierson.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Ranch life -- Drama; Western films; Action and adventure films; Feature films; Internet videos; Streaming video